Estudo da percepção pública sobre captura e armazenamento geológico de CO2 (CCS) no Espírito Santo - Lima, Pâmela Rossoni (2018)
Cleaner energy production associated with population awareness for sustainable consumption becomes a challenge for the 21st century. However, most of the energy consumed worldwide comes from the burning of fossil fuels (coal, oil and natural gas), responsible for the generation of greenhouse gases, the most abundant being: CO2, CH4 e N2O. However, carbon dioxide (CO2) is the gas that contributes most to global warming, accounting for 58% of total global GHG emissions (IEA, 2017). In Brazil, this gas represents 73% of total emissions (SEEG, 2018). In this context, it includes the technology of Carbon Capture and Storage (CCS), which aims to contribute to the reduction of CO2 emissions. This dissertation aims to analyze the public perception of CCS technology in the state of Espírito Santo, more specifically in the cities of Vitória (capital) and São Mateus (interior), relating it to environmental awareness of citizens in the context of climate change. This study had as methodological strategy the obtaining of data through personal interviews with 400 inhabitants in each city. A descriptive analysis of the results was carried out in order to substantiate the differences between the answers obtained in the capital and in the interior. In addition, hypothesis tests were also carried out with different population groups to evaluate the existence of an association between the qualitative variables. It was observed that most respondents in both cities feel the climate changes around the place where they live; that fossil fuels contribute, in part, to global warming; that deforestation is the way that contributes most to increasing global warming in Brazil and that climate change can aggravate problems related to the scarcity of drinking water. Respondents from both cities have voiced concerns about environmental issues, however, there is a low willingness to pay tax on global warming and low membership to leave their cars and use public transport. It was verified that the population of the two cities does not have knowledge about CCS, however, knowing the technology demonstrated support attitudes for the development of the same in Brazil by the government. Hypothesis tests revealed that in the city of São Mateus there are significant differences among people concerned about climate change due to the degree of schooling. The difference is between the upper and lower levels, and people with the highest level of education are more sensitive to these issues.